2021
DOI: 10.1128/mbio.00557-21
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Viral Evolution Identifies a Critical Residue in the Alphaherpesvirus Fusion Glycoprotein B Ectodomain That Controls gH/gL-Independent Entry

Abstract: Herpesvirus entry and spread requires fusion of viral and host cell membranes, which is mediated by the conserved surface glycoprotein B (gB). Upon activation, gB undergoes a major conformational change and transits from a metastable prefusion to a stable postfusion conformation. Although gB is a structural homolog of low-pH-triggered class III fusogens, its fusion activity depends strictly on the presence of the conserved regulatory gH/gL complex and nonconserved receptor binding proteins, which ensure that f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 62 publications
1
10
0
Order By: Relevance
“…In contrast to WT HSV-1 gB, which shows a partial transition, WT VZV gB on EVs fully transitions to the postfusion conformation suggesting that VZV gB is a highly metastable fusogen. In addition to the membrane, our previous studies have demonstrated the likely requirement of the gH-gL heterodimer to keep VZV gB locked in place 47 , which is also supported by recent findings with pseudorabies virus (PrV) and HSV-1 gB 810 . The overall requirement for the structural integrity of the gB DIII central helix was demonstrated by consequences of the proline mutations at E526 and V528 for gB-mediated fusion, gB maturation, viral replication and cell-cell spread.…”
Section: Discussionsupporting
confidence: 77%
“…In contrast to WT HSV-1 gB, which shows a partial transition, WT VZV gB on EVs fully transitions to the postfusion conformation suggesting that VZV gB is a highly metastable fusogen. In addition to the membrane, our previous studies have demonstrated the likely requirement of the gH-gL heterodimer to keep VZV gB locked in place 47 , which is also supported by recent findings with pseudorabies virus (PrV) and HSV-1 gB 810 . The overall requirement for the structural integrity of the gB DIII central helix was demonstrated by consequences of the proline mutations at E526 and V528 for gB-mediated fusion, gB maturation, viral replication and cell-cell spread.…”
Section: Discussionsupporting
confidence: 77%
“…Third, it is unknown how the signal from the destabilized gB CTD trimer is transmitted to the gB ectodomain on the other side of the membrane. A recent study suggested that a conserved regulatory helix in the gB ectodomain proximal to the membrane may be involved in the transduction of the triggering signal from the cytoplasmic domain to the ectodomain [ 63 ]. Further studies are needed to decipher how gH/gL interacts with and activates gB and how the gB structure changes in response to this interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Second, it is unknown how the signal from the destabilized gB CTD trimer is transmitted to the gB ectodomain on the other side of the membrane. A recent study suggested that a conserved regulatory helix in the gB ectodomain proximal to the membrane may be involved in the transduction of the triggering signal from the cytoplasmic domain to the ectodomain [56]. Further studies are needed to decipher how gH/gL interacts with and activates gB and how the gB structure changes in response to this interaction.…”
Section: Discussionmentioning
confidence: 99%